Determinants of Capital Structure: Evidence from Coal Mining Companies Listed on the Indonesia Stock Exchange - Bako, Seven Marganda (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to analyze the factors influencing the capital structure of coal mining companies listed on the Indonesia Stock Exchange (IDX) during the 2014–2018 period. The independent variables studied include profitability, asset structure, liquidity, and company size, while the dependent variable is capital structure, proxied by the debt-to-equity ratio (DER). The research method uses panel data regression analysis with a random effects model selected based on model feasibility testing. The data used are secondary data from the companies' annual financial reports. The results of the study indicate that profitability and asset structure do not significantly influence capital structure. Conversely, liquidity has a negative and significant effect on capital structure, meaning that the higher a company's liquidity level, the lower its debt usage. Firm size does not significantly influence capital structure. Overall, the independent variables in this study explain 43.47% of the variation in capital structure, while the remaining 56.53% is influenced by factors outside the research model. These findings imply that coal companies tend to prioritize internal funding over external funding, in accordance with the Pecking Order Theory. Financial managers need to consider liquidity factors when determining capital structure policies to maintain efficiency and ensure business continuity.